2016
DOI: 10.1016/j.jpeds.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Controlled Attenuation Parameter and Liver Biopsy to Assess Hepatic Steatosis in Pediatric Patients

Abstract: Objective To assess whether the degree of steatosis as determined by Controlled Attenuation Parameter (CAP) measurements correlates with that observed on liver biopsies in a single-center pediatric and young adult cohort. Study design This was a cross-sectional study in patients undergoing liver biopsy as part of standard clinical care between January 25, 2012, and April 1, 2015 at Boston Children’s Hospital. Eligible patients, with a variety of liver diseases, had CAP measurements within 1 year of biopsy. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 19 publications
5
75
1
1
Order By: Relevance
“…CAP is a new noninvasive method that has shown promise in the assessment of steatosis also in pediatric patients. Recently, in a study performed in a small series of children in whom liver biopsy was carried out for clinical indications, a cut point of 225 dB/m for predicting steatosis has been identified, with 0.87 sensitivity, 0.83 specificity, and AUROC 0.93 [7]. The results of our study show that a CAP cutoff value of 249 dB/m rules in liver steatosis with a very high specificity.…”
Section: Discussionsupporting
confidence: 53%
“…CAP is a new noninvasive method that has shown promise in the assessment of steatosis also in pediatric patients. Recently, in a study performed in a small series of children in whom liver biopsy was carried out for clinical indications, a cut point of 225 dB/m for predicting steatosis has been identified, with 0.87 sensitivity, 0.83 specificity, and AUROC 0.93 [7]. The results of our study show that a CAP cutoff value of 249 dB/m rules in liver steatosis with a very high specificity.…”
Section: Discussionsupporting
confidence: 53%
“…However, data in AYAs are limited. A recent study compared CAP measurements with steatosis on liver biopsy in adolescents (mean age, 16) and noted that CAP can detect steatosis and discriminate between its grades . In addition, a study in children and adolescents has shown that VCTE accurately identifies those without fibrosis and subjects with AF (F ≥ 3), but does not differentiate well between lower stages of fibrosis .…”
Section: Diagnostic Modalitiesmentioning
confidence: 99%
“…Fibrosis was staged from F0 to F4, F0: absence of fibrosis; F1: perisinusoidal or portal fibrosis; F2: both perisinusoidal and portal fibrosis; F3: septal or bridging fibrosis; and F4 indicate hepatic cirrhosis (17). The reported CAP and LSM measurement was the median of 10 measurements (18). The intraobserver agreement ICC was 0.98 for FibroScan results (19).…”
Section: Data Collectionmentioning
confidence: 99%